Drp1-driven fragmentation of scleral mitochondria promotes myopia development - Zhenqi Guan; Wenting Li; Shengcong Liu; Xingxing Yang; Yuejia Peng; Long Ye; Luyao Wang; Yuan Lu; Sisi Dong; Huihui Liu; Jian Yuan; Jianzhong Su; et al. (Proceedings of the National Academy of Sciences, 2026)
The global epidemic of myopia constitutes a growing public health concern worldwide. Myopia development is characterized by pathological scleral remodeling through fibroblast-myofibroblast transdifferentiation (FMT) and extracellular matrix (ECM) degradation. Since myopia is progressive, the development of sustainable and safe preventive interventions is imperative. While mitochondrial dynamics critically regulate fibrotic processes in other organs, their role in scleral homeostasis has remained unexplored. Here, we identify pathological mitochondrial fragmentation, caused by increased mitochondrial fission, as a key driver of myopia progression. Using two mammalian animal models, we demonstrate that both genetic and pharmacological enhancement of mitochondrial fission (inducing mitochondrial fragmentation) exacerbates collagen loss and accelerates axial elongation, whereas genetic and pharmacological inhibition of mitochondrial fission prevents collagen degradation and attenuates myopia progression. Hypoxia-induced FMT in cultured human scleral fibroblasts (HSFs) requires activation of mitochondrial fission, revealing overproduction of reactive oxygen species (ROS) as the downstream effector on HSFs and in both animal models. Our multilevel analyses identify the mitochondrial fission-ROS axis as a key pathway linking scleral hypoxia to ECM remodeling. Lycopene, a naturally occurring carotenoid antioxidant, significantly attenuated scleral ROS levels and was found suitable for long-term application, highlighting its potential as a therapeutic agent for myopia control. Collectively, these findings have identified a therapeutic target and agent for controlling myopia progression.